1953
DOI: 10.1136/bmj.1.4814.799
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Cancer of Stomach and the ABO Blood Groups

Abstract: It was shown by Stocks (1950) Legon (1951Legon ( , 1952 in attempts to correlate the geographical variations in the mortality from gastric cancer with variations in the organic content of the soil.It occurred to one of us that there might be a correlation between the high northern incidence of cancer of the stomach and the genetic differences which are reflected in the ABO blood groups, the frequency of blood group 0 being greater, that of A less, in northern than in southern populations, B and AB being sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
279
5
11

Year Published

1954
1954
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 587 publications
(307 citation statements)
references
References 3 publications
12
279
5
11
Order By: Relevance
“…Possible associations between ABO blood group and the risk of some epithelial malignancies, including pancreatic cancer and gastric cancer have been reported previously (Aird et al, 1953;Amundadottir et al, 2009;Wolpin et al, 2009;Greer et al, 2010;Iodice et al, 2010). Aird et al (1953) reported a relationship between gastric cancer and ABO blood groups in the 1950s.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Possible associations between ABO blood group and the risk of some epithelial malignancies, including pancreatic cancer and gastric cancer have been reported previously (Aird et al, 1953;Amundadottir et al, 2009;Wolpin et al, 2009;Greer et al, 2010;Iodice et al, 2010). Aird et al (1953) reported a relationship between gastric cancer and ABO blood groups in the 1950s.…”
Section: Discussionmentioning
confidence: 77%
“…Aird et al (1953) reported a relationship between gastric cancer and ABO blood groups in the 1950s. The frequency of blood group A was greater and O was lower in patient with gastric cancer than normal population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it has been reported that genetic changes on the chromosome 9 may have an effect on the release of ABO blood group antigens. Several studies have shown that changes in the ABO/Lewis blood group antigens may be associated with the malignant transformation for some tumors (Aird et al, 1953;Jordan and Lynch, 1983;Rolfe et al, 2002;Adamian, 2005;Tursen et al, 2005;El Hajj et al, 2007;Hosoi, 2008;Edgren et al, 2010;Iodice et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In 1953, Aird et al (1953) first reported such a relationship between A blood group and gastric cancer. Subsequent studies confirmed that the incidence of gastric cancer was higher (nearly 20%) in individuals with A blood group.…”
Section: Discussionmentioning
confidence: 99%